PENINGKATAN EKONOMI MASYARAKAT MELALUI TARI BALUSE: PERAN KEARIFAN LOKAL NIAS SELATAN DI DESA WISATA HILIMONDREGERAYA - Baziduhu Laia; Midarwati Gaurifa; Raihfan Trielman Lature; Fransiskus Gaurifa; Tatema Telambanua; Selfi Yanti Bali (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
This study aims to explore the role of Tari Baluse as a cultural heritage in empowering the local economy through the development of tourism based on local wisdom in Hilimondregeraya Tourism Village, South Nias. Tari Baluse is a traditional war dance rich in historical value, symbolizing courage and the cultural identity of the Nias people. In the context of tourism, performances of Tari Baluse serve as a major attraction for both domestic and international tourists. This research employs a qualitative and quantitative approach, with data collected through observation, in-depth interviews, and surveys with artists, local residents, and small business actors. The findings indicate that Tari Baluse significantly contributes to increasing community income, particularly through the growth of micro, small, and medium enterprises (MSMEs) such as handicrafts, local culinary businesses, and tour guide services. The active participation of the community—especially women and youth—in culture-based creative economic activities also demonstrates a positive social impact. However, challenges remain, particularly in terms of limited infrastructure and promotional efforts. The study recommends strengthening local tourism governance, enhancing community capacity through training, and optimizing digital promotion as strategic steps toward sustainable economic development and cultural preservation.